E-Media Use and Preferences for Physical Activity and Public Health Information: Results of a Web-Based Survey. Issue 4 (July 2018) - Jake-Schoffman, Danielle E.; Wilcox, Sara; Kaczynski, Andrew T.; Turner-McGrievy, Gabrielle; Friedman, Daniela B.; West, Delia S.
Abstract : Context: As social media (eg, Twitter) continues to gain widespread popularity, health research and practice organizations may consider combining it with other electronic media (e-media) channels (eg, Web sites, e-newsletters) within their communication plans. However, little is known about added benefits of using social media when trying to reach public health audiences about physical activity. Objective: Learn about current use and preference for e-media communication channels among physical activity researchers and practitioners. Design: A Web-based survey was used, open for responses from August 20, 2015, through January 5, 2016. Survey participation was voluntary and anonymous. The survey was advertised through multiple channels targeting physical activity researchers and practitioners, including announcements on professional listservs and in e-newsletters, Twitter, and posts on Facebook pages of public health organizations. Setting and Participants: A total of 284 survey respondents had complete data. Main Outcome Measures: Typical use of e-media to receive, seek out, and share information about physical activity and health and what appeals to researchers and practitioners for professional use. Results: Most respondents preferred non–social media channels to social media and these preferences did not differ widely when examining subgroups such as researchers versus practitioners or social media users versus nonusers. There were few differences by respondent demographics, though younger respondents reported using social media more than older respondents. However, limiting analyses to respondents who identified as social media users, only about 1% of respondents ranked social media sources as their preferred channels for information; thus, most people would continue to be reached if communication remained largely via non–social media e-media channels. Conclusions: The present study supports growing evidence that careful surveying of a target audience should be undertaken when considering new communication channels, as preference and use may not support the effort required to create and maintain resource-intensive strategies like social media. Abstract : Supplemental Digital Content is Available in the Text.